Unveiling The Impact of Inquiry-Based Learning: A Meta-Analysis of Student Learning Outcomes - Harleni Harleni; Ganefri Ganefri; Asmar Yulastri; M Giatman; Dedy Irfan; Hansi Effendi (STAI Hubbulwathan Duri, 2025)
Inquiry-based learning (IBL) has been increasingly adopted in education to foster students’ conceptual understanding and critical thinking. However, existing research shows varying results regarding its effectiveness, ranging from significant positive effects to no impact. This study aims to systematically evaluate the impact of IBL on student learning outcomes through a meta-analytic approach. A meta-analysis was conducted on empirical studies published between 2020 and 2024. The study followed the PRISMA protocol, including three stages: identification, screening, and inclusion. A total of 21 relevant studies were selected and analyzed using JASP software to ensure accuracy in calculating effect sizes and interpreting findings. The meta-analysis revealed that inquiry-based learning has a small but significant overall effect on student learning outcomes (effect size: d = 0.444). The impact was particularly evident in science and mathematics education. Additionally, moderating variables such as educational level, instructional design, and student engagement were found to influence the effectiveness of IBL. While the overall effect size is modest, the findings confirm that IBL can positively contribute to student achievement. These results support the continued use and further development of inquiry-based approaches in modern educational contexts. The study provides evidence-based insights for educators, researchers, and policymakers seeking to optimize teaching strategies for 21st-century learning environments.